Social change and political transformation - Rootes, Chris; Davis, Howard H. (UCL Press, 1994)
Introduction / Chris Rootes -- 1. European countries in a post-national era / Alain Touraine -- 2. The European Community: regime-building and institutionalization of criteria for rationality / Rainer Lepsius -- 3. Harmonization and the art of European government / Andrew Barry -- 4. Theses on a post-military Europe: conscription, citizenship and militarism after the Cold War / Martin Shaw -- 5. Changing attitudes in the European Community / Sheena Ashford and Loek Halman -- 6. Support for new social movements in five western European countries / Dieter Fuchs and Dieter Rucht -- 7. Environmentalism in Europe: an east-west comparison / Petr Jehlicka -- 8. Order, crisis and social movements in the transition from state socialism / Nick Manning -- 9. Intellectuals and democratization in Hungary / Andras Bozoki -- 10. State and society in Poland / Mira Marody -- 11. Some thoughts on trust, collective identity, and the transition from state socialism / Adam Seligman
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Konferenzschrift -- 1992 -- Berlin; Europa; Politischer Wandel; Sozialer Wandel; Europäische Union